Quiet fire: memoirs of older gay men - Vacha, Keith (The Crossing Press gay series, 1985)
Introduction / Don Clark -- Don the longshoreman -- Todd Grison -- Alan Williams -- Bob Basker -- Will Whiting -- Richard Von Berg -- George Morrison -- Andrew Weiler -- Raymond Friedman -- Jonathan West -- David Bowling -- Al Hoskins -- John Hall -- Josh Holland -- Greg Aarons -- Jordan Lee -- Tony Isaac -- Summary / Keith Vacha.